Trends in Australian and Canadian public service perceptions from an employee survey perspective - Althaus, Catherne; Rath bone, Emily; Evans, Bryan (2012)
A comparative analysis of results from the 2011 Institute of Public Administration Australia and Institute of Public Administration of Canada surveys of public service leaders is mapped against related public sector employee survey tools results. Alignment of past results with current leader perceptions shows remarkable consistency across the jurisdictions over time. This overarching coherence points to two broad hypotheses: either senior public service leaders possess a common set of preoccupations in the modern global context, or a more critical perspective would question the shortcomings of the instruments given that remarkable change has occurred that one would expect should have driven result variance. Regardless of the conclusion brought to this preliminary analysis, ongoing identification and mapping of senior leader perceptions through such tools is celebrated as an important contribution to ongoing public service organizational health. - Reproduced.
Keywords: Civil service